2017
DOI: 10.1074/mcp.m116.064741
|View full text |Cite
|
Sign up to set email alerts
|

Human Antiviral Protein IFIX Suppresses Viral Gene Expression during Herpes Simplex Virus 1 (HSV-1) Infection and Is Counteracted by Virus-induced Proteasomal Degradation

Abstract: The interferon-inducible protein X (IFIX), a member of the PYHIN family, was recently recognized as an antiviral factor against infection with herpes simplex virus 1 (HSV-1). IFIX binds viral DNA upon infection and promotes expression of antiviral cytokines. How IFIX exerts its host defense functions and whether it is inhibited by the virus remain unknown. Here, we integrated live cell microscopy, proteomics, IFIX domain characterization, and molecular virology to investigate IFIX regulation and antiviral func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 53 publications
2
43
0
Order By: Relevance
“…Because nucleic acid sensing would not be involved in pro-inflammatory cytokine-stimulated mRNA induction, we reasoned that PYHIN1 may directly regulate promoter induction of IL-6 and TNF␣. This would be consistent with the fact that another PYHIN protein, IFI16, has been shown to directly modulate both viral and host gene promoters in certain circumstances (42,43), and with the fact that, like IFI16, PYHIN1 can be detected in the nucleus (31,32). Furthermore, the fact that PYHIN1 was required for both IL-1and TNF␣-mediated IL-6 induction ( Fig.…”
Section: Pyhin1 Regulates the Il-6 And Tnf␣ Gene Promoterssupporting
confidence: 81%
See 2 more Smart Citations
“…Because nucleic acid sensing would not be involved in pro-inflammatory cytokine-stimulated mRNA induction, we reasoned that PYHIN1 may directly regulate promoter induction of IL-6 and TNF␣. This would be consistent with the fact that another PYHIN protein, IFI16, has been shown to directly modulate both viral and host gene promoters in certain circumstances (42,43), and with the fact that, like IFI16, PYHIN1 can be detected in the nucleus (31,32). Furthermore, the fact that PYHIN1 was required for both IL-1and TNF␣-mediated IL-6 induction ( Fig.…”
Section: Pyhin1 Regulates the Il-6 And Tnf␣ Gene Promoterssupporting
confidence: 81%
“…This led to an important new insight into PYHIN1 function, namely that it was required for optimal IL-6 and TNF␣ transcriptional induction after cytokine stimulation of cells. Hence, similar to IFI16, PYHIN1 has now been implicated in DNA sensing (31), viral restriction (32), and host immune gene regulation (this paper). IFI16 was previously shown to be required for maximal promoter induction of type I IFNs and IFN-stimulated genes, but not IL-6, in human THP-1 monocytes (42).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…of pre-replicative sites containing the helicase-primase complex, appearing as punctate foci in the nucleus [34]. ICP0, a HSV IE protein, binds to several cellular proteins as well as viral promoters resulting in increased expression of viral E and L genes.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, the vesicle-containing secretome contained components of the translational machinery, leading the authors to propose a model in which secretion and inhibition of translation plays a role in host defense against bacteria. Also, working on immune response, Crow and Cristea provide insights into the antiviral functions of the interferon-inducible protein IFIX in response to infection of primary human fibroblasts with the DNA virus HSV-1 (15). Using protein interaction studies, MS, microscopy, and functional assays, IFIX is found to have a dual role in defense via both stimulation of innate immune response and inhibition of virus gene expression.…”
mentioning
confidence: 99%